PENGELOLAAN WISATA OLEH PEMERINTAH DESA: (STUDI KASUS PENGEMBANGAN OBJEK WISATA AIR TERJUN WEE KACURA DI DESA TEMA TANA KECAMATAN WEWEWA TIMUR KABUPATEN SUMBA BARAT DAYA) - Bora, Edwin (SINERGI : Jurnal Riset Ilmiah, 2025)
Tourism in Indonesia has experienced significant development from the increasing number of tourists visiting various tourist destinations. To make a major contribution to the national economy, create jobs, reduce poverty, and act as a medium in creating social harmony, especially in areas that have extraordinary natural potential, such as in Tema Tanah Village, Wewewa Timur District, Southwest Sumba Regency, which is a village with amazing natural tourism potential, including Waikelo Sawah and Wee Kacura Waterfall. The purpose of the study was to describe and analyze the development of the management of the Terun Wee Kacura water tourism object by the Village government. The type of research is descriptive with a qualitative approach. The sample size is 5 respondents, namely the Head of Tema Tana Village, Youth Leaders, Traditional Leaders, Community Leaders, Tourist Visitors. The results of the study show complex dynamics but open up great opportunities for the development of Tema Tanah Village. Positive impacts such as increased economic activity of residents, the growth of the spirit of mutual cooperation, attention to environmental sustainability, increased tourist visits. Limitations caused by the rejection of some landowners regarding the development of infrastructure and supporting facilities, such as road access, parking lots, public toilets around Wee Kacura Waterfall are inhibiting factors in optimizing this tourism so that it has not been fully explored. So the government is still trying to conduct face-to-face dialogue with traditional leaders and landowners to become a strategic space to find joint solutions. And the positive response from tourists also strengthens Wee Kacura's position as a potential destination that requires a better and more inclusive management touch.